Movements and Area Use of Belugas, Delphinapterus leucas, in a Subarctic Alaskan Estuary - Hobbs, R.C.; Laidre, K.L.; Vos, D.J.; Mahoney, B.A.; Eagleton, M. (ARCTIC, 2010)
Seasonal movements of 14 belugas in Cook Inlet, Alaska, were monitored by satellite telemetry between July and March in 2000–03. Whales used waters in the upper Cook Inlet intensively between summer and late autumn and dispersed to mid-inlet offshore waters during winter months. All whales remained in Cook Inlet the entire time they were tracked, and several whales were tracked through March. During summer and early fall, movements were clearly concentrated in specific areas, generally river mouths or bays, where whales were likely feeding on fish runs. Average daily travel distances ranged from 11 to 30 km per day. Monthly home ranges, estimated using the 95% kernel probability distribution of average daily positions, were smallest in August (982 km2), increased throughout autumn, and peaked in winter (reaching approximately 5000 km2). The seasonal variation in distribution and movement patterns displayed by belugas in Cook Inlet affect the sighting rates and seasonal abundance estimates obtained for this depleted population. Les déplacements saisonniers de 14 bélugas du détroit de Cook, en Alaska, ont fait l’objet d’une surveillance au moyen d’un émetteur par satellite entre les mois de juillet et mars 2000 à 2003. Cela a permis de remarquer que les baleines se tenaient beaucoup dans les eaux de la partie supérieure du détroit de Cook de l’été jusqu’à la fin de l’automne, mais qu’elles se dispersaient dans les eaux du large du milieu du détroit pendant les mois d’hiver. Toutes les baleines sont restées dans le détroit de Cook pendant toute la durée de surveillance, et plusieurs baleines ont été suivies jusqu’au mois de mars. L’été et au début de l’automne, les déplacements étaient nettement concentrés dans des endroits spécifiques, généralement dans les embouchures ou les baies, où les baleines se nourrissaient probablement de poissons. En moyenne, les baleines se déplaçaient sur des distances variant de 11 à 30 km par jour. C’est en août que le domaine vital mensuel, estimé par la méthode du noyau en ...